2006
DOI: 10.1007/s11249-006-9078-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of protein adsorption on the friction behavior of ultra-high molecular weight polyethylene

Abstract: Medical-grade UHMWPE samples with two different surface finishing treatments, milling and melting/reforming were exposed to 10% bovine serum albumin solution and their friction responses were quantified using atomic force microscopy. The observed friction increase upon exposure to proteins was attributed to the formation of a layer of denatured proteins on the surface. Changing the crystallinity and surface energy of UHMWPE affected the protein adsorption mechanism and the resulting increase in friction behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 43 publications
(45 reference statements)
0
21
0
Order By: Relevance
“…This expectation is strengthened by our own previous results for surface textured ceramic-steel contacts [41]. As this study was performed with isooctane instead of PAO, elucidating how lubricants with different viscosities and molecular weights [42] influence the optimum texturing parameters is part of our ongoing research efforts. A laser texturing parameter that will be systematically studied in the future is the cross-sectional profile of the dimples.…”
Section: Discussionmentioning
confidence: 62%
“…This expectation is strengthened by our own previous results for surface textured ceramic-steel contacts [41]. As this study was performed with isooctane instead of PAO, elucidating how lubricants with different viscosities and molecular weights [42] influence the optimum texturing parameters is part of our ongoing research efforts. A laser texturing parameter that will be systematically studied in the future is the cross-sectional profile of the dimples.…”
Section: Discussionmentioning
confidence: 62%
“…Karuppiah et al also found an increase in boundary friction as function of protein concentration. 21 However, they report, using the same surface as Widmer et al 24 a higher friction on hydrophilic UHMWPE (ultrahigh molecular weight polyethylene used in total joint replacements) surfaces instead of on hydrophobic UHMWPE. Our friction experiments confirm the observed higher friction as function of protein concentration (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, the boundary/mixed regimes are often crucial in the field of bio-lubrication, e.g., in joint and prosthetic material lubrication. [19][20][21][22][23][24] Below, we discuss some of the relevant papers from the areas of hydrodynamic emulsion lubrication and bio-lubrication, and relate them to the work presented here.…”
Section: Discussionmentioning
confidence: 99%
“…29 It has been postulated that the formation of thick, multilayer protein films plays an important role in determining the friction coefficient of artificial hip implants. 8,12,23,[30][31][32][33] Albumin is sensitive to many factors including heat, protein concentration, salt concentration, and pH, and aggregates through hydrophobic interactions in solution over time to form solid, insoluble particles. 34,35 These particles are then deposited on the surface.…”
Section: Discussionmentioning
confidence: 99%